2016
DOI: 10.3390/ijms17101761
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intracellular Lipid Logistics in the Preferential Usage of Very Long Chain-Ceramides in Glucosylceramide

Abstract: Ceramide is a common precursor of sphingomyelin (SM) and glycosphingolipids (GSLs) in mammalian cells. Ceramide synthase 2 (CERS2), one of the six ceramide synthase isoforms, is responsible for the synthesis of very long chain fatty acid (C20–26 fatty acids) (VLC)-containing ceramides (VLC-Cer). It is known that the proportion of VLC species in GSLs is higher than that in SM. To address the mechanism of the VLC-preference of GSLs, we used genome editing to establish three HeLa cell mutants that expressed diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…Metabolic labeling experiments using D-[1-14 C]galactose, including mild alkaline methanolysis, were performed as described previously (59). Cells (3 3 10 5 /well in a 6-well plate) were cultured overnight at 37°C and then incubated for 16 h with 7.4 kBq of D-[1-14 C]galactose in Opti-MEM with 1% Neutridoma-SP (Roche).…”
Section: Metabolic Labeling Of Glycolipids and Tlc Analysismentioning
confidence: 99%
“…Metabolic labeling experiments using D-[1-14 C]galactose, including mild alkaline methanolysis, were performed as described previously (59). Cells (3 3 10 5 /well in a 6-well plate) were cultured overnight at 37°C and then incubated for 16 h with 7.4 kBq of D-[1-14 C]galactose in Opti-MEM with 1% Neutridoma-SP (Roche).…”
Section: Metabolic Labeling Of Glycolipids and Tlc Analysismentioning
confidence: 99%
“…Ceramides are primarily generated de novo in the ER, but also from the hydrolysis of sphingomyelin at the plasma membrane and via sphingosine salvage in the mitochondria. Subcellular transport mechanisms, particularly to the Golgi where ceramides are further metabolised, show preferential targeting for specific ceramide species (Kumagai et al 2005, Konstantynowicz-Nowicka et al 2015, Kakazu et al 2016, Yamaji et al 2016, indicating the likelihood of differential function according to spatial distribution. Temporal studies have further found that ceramide species in the nucleus are differentially composed and regulated to those found in mitochondria (Aviram et al 2016).…”
Section: Subcellular Localisationmentioning
confidence: 99%
“…This paradox might be explained by recent findings. First, CERT may preferentially transport ceramide subspecies that are preferential substrates for SMSs . Second, when GlcCer synthase is partitioned into the same Golgi cisterna as SMS1, the activity of the former enzyme is inhibited .…”
mentioning
confidence: 99%